2018
DOI: 10.21079/11681/27867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lightweight Airfield Matting for the AMX Program

Abstract: Airfield matting systems are used for the expedient construction of temporary airfields and the expansion of existing airfields to provide temporary airfield operating surfaces for military aircraft. The primary airfield matting system used by the U.S. Military is the AM2 airfield matting system. Although the AM2 matting system has proved to be successful for supporting modern aircraft, it is difficult to transport by air because of its size and weight. The AMX program was initiated by the U.S. Air Force to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…for the PSA-FT-R. Additionally, reported that the Modified Light-Duty AM2 provided excellent performance with RPA loads. Garcia and Hoffman (2018) reported poor performance of the S46 and ALMATS when tested on a CBR of 6 and trafficked under F-15E traffic. Fewer than 50 passes to failure were supported by either mat system.…”
Section: Results and Analysismentioning
confidence: 93%
See 3 more Smart Citations
“…for the PSA-FT-R. Additionally, reported that the Modified Light-Duty AM2 provided excellent performance with RPA loads. Garcia and Hoffman (2018) reported poor performance of the S46 and ALMATS when tested on a CBR of 6 and trafficked under F-15E traffic. Fewer than 50 passes to failure were supported by either mat system.…”
Section: Results and Analysismentioning
confidence: 93%
“…For over a decade, commercial matting systems have been investigated as part of the AMX program (Rushing et al 2009;Garcia et al 2012;Rushing et al 2012). Details for the most recent testing performed at the Engineer Research and Development Center (ERDC) under this program can be found in Garcia and Hoffman (2018).…”
Section: Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…AM-2 is a versatile system that can handle multiple kinds of aircraft (6)(7)(8)(9), but poses logistical constraints arising from size and weight, and cannot be manufactured in theater or on demand. Alternative matting solutions have been developed and are constructed from lighter weight materials, such as fiberglass (10), composite materials (2,11), and polymers (12)(13)(14). While these mats have yet to replace AM-2, they demonstrate that polymer-based matting can serve as a viable and versatile alternative.…”
mentioning
confidence: 99%